GRUPOS ESTRATÉGICOS EN EL SECTOR PERIODISTICO Panorama en la Ciudad de Lima - Antonio, Javier (1995)
Describes and interprets the behavior of the national journalistic sector from the strategic groups that compete in this industry. For this, the market was segmented based on two variables: type of reader and the way of presenting the information, and a matrix of strategic groups was elaborated, according to three other variables: technology, operating leverage and specialization, to identify generic strategies developed by companies in this sector. A high correlation was found between type of information and type of reader (formal-style newspapers are aimed at traditional readers, while informal ones are aimed at "chicha" readers); having its own press as the highest mobility barrier, since this represents a significant investment for any reader company; vulnerability of all groups to substitute products; high rivalry between newspapers for some of them sharing their target markets; and leverage as the strategy of most newspapers that reach a high level of sales.